4E‐BP1 regulates the sensitivity of human glioma cells to chemotherapy through PI3K/Akt/mTOR‐independent pathway. Issue 3 (20th December 2013) - Zhu, Hui‐Li; Xie, Si‐Ming; Fang, Mao; Zhang, Ji‐Jun; Weng, Ze‐Ping; Zhong, Xue‐Yun
<x xml:space="preserve">Abstract</x> Drug resistance is one of the most formidable obstacles for treatment of glioma. Eukaryotic initiation factor 4E‐binding protein (4E‐BP1), a key component in the rate‐limiting step of protein translation initiation, is closely associated with poor prognosis in multiple tumor types. However, it is unclear whether 4E‐BP1 is involved in the drug resistance of human glioma. Herein we show that the expression of 4E‐BP1 in human SWOZ2‐BCNU drug‐resistant glioma cells is significantly lower than that of the parent SWOZ2 cell line. Moreover, down‐regulation of 4E‐BP1 by short interfering RNA significantly impaired the sensitivity of SWOZ2 and U251 cells to carmustine (BCNU). Furthermore, overexpression of 4E‐BP1 with plasmid transfection regained this sensitivity. Clinical studies showed that the expression levels of 4E‐BP1 in primary glioma tissues were markedly higher than those of recrudescent glioma tissues. Taken together, our results suggest that 4E‐BP1 is a novel protein that contributes to acquired drug resistance and it may be a potential target for reversing drug resistance in human glioma.